2014
DOI: 10.1007/s10255-014-0405-9
|View full text |Cite
|
Sign up to set email alerts
|

On the existence and uniqueness of solutions to stochastic differential equations driven by G-Brownian motion with integral-Lipschitz coefficients

Abstract: Abstract. In this paper, we study the existence and uniqueness of solutions to stochastic differential equations driven by G-Brownian motion (GSDEs) with integral-Lipschitz conditions on their coefficients.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 21 publications
1
51
0
1
Order By: Relevance
“…The results are consistent with those from previous studies 38 and the stability of multi-armed spirals can be further discussed as shown in Ref. 42. These findings explain why multi-spiral waves seldom emerge and are not as common as spiral waves with a single arm.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The results are consistent with those from previous studies 38 and the stability of multi-armed spirals can be further discussed as shown in Ref. 42. These findings explain why multi-spiral waves seldom emerge and are not as common as spiral waves with a single arm.…”
Section: Discussionsupporting
confidence: 94%
“…Zaritski et al 41 numerically investigated the parameter region for generating multi-armed spiral wave with different arm numbers. Bai et al 42 gave numerical analysis about the multi-armed spiral waves in gas discharge system. As reported by Ref.…”
Section: Introductionmentioning
confidence: 99%
“…To verify that {Ȳ n } n∈N is a Cauchy sequence in S Indeed, since w h is a concave function, by Lemma 2.12 in Bai and Lin [2], we have…”
Section: The Existence Of Solutions To Discrete Gbsdesmentioning
confidence: 99%
“…The unique solution to (1.1) is constructed through successive approximation. It is worthwhile to mention that non-Lipschitz conditions have been studied in [2]. But our assumption is more general than theirs.…”
Section: Introductionmentioning
confidence: 96%